Loss of T-Cell Multifunctionality and TCR-Vβ Repertoire Against Epstein-Barr Virus Is Associated With Worse Prognosis and Clinical Parameters in HIV+ Patients - Hernández, Diana M.; Valderrama, Sandra; Gualtero, Sandra; Hernández, Catalina; López, Marcos; Herrera, Maria Victoria; Solano, Julio; Fiorentino, Susana; Quijano, Sandra (Frontiers in Immunology, 2018)
Epstein-Barr virus (EBV) is an oncogenic virus associated with the development of aggressive and poor-prognosis B-cell lymphomas in patients infected with human immunodeficiency virus (HIV+ patients). The most important risk factors for these malignancies include immune dysfunction, chronic immune activation, and loss of T-cell receptor (TCR) repertoire. The combination of all these factors can favor the reactivation of EBV, malignant cell transformation, and clinical progression toward B-cell lymphomas. The overarching aim of this study was to evaluate the frequency, phenotype, functionality, and distribution of TCR clonotypes for EBV-specific T-cell subpopulations in HIV+ patients at different clinical stages and for HIV+ patients with B-cell lymphoma, as well as to establish their association with clinical variables of prognostic value. Factors were studied in 56 HIV+ patients at different clinical stages and in six HIV+ subjects with diagnosed B-cell lymphoma. We found a significant decrease in all subpopulations of EBV-specific CD4+ T cells from HIV+ patients at stage 3 and with B-cell lymphoma. EBV-specific effector CD8+ T cells, particularly effector memory cells, were also reduced in HIV+ patients with B-cell lymphoma. Interestingly, these cells were unable to produce IFN-γ and lacked multifunctionality in HIV+ patients. The TCR-Vβ repertoire, which is key for protection against EBV in healthy individuals, was less diverse in HIV+ patients due to a lower frequency of TCR-Vβ2+, Vβ4+, Vβ7.1+, Vβ9+, Vβ13.6+, Vβ14+, Vβ17+, Vβ22+ CD4+, Vβ14+, and Vβ17+ CD8+ T cells. HIV+ patients with positive plasma EBV loads (EBV+HIV+) had a noteworthy decrease in the levels of both TNF-α+ and multifunctional TNF-α+/IL-2+ and TNF-α+/IFN-γ+ CD8+ T cells. Altogether, our findings demonstrate that HIV+ patients have significant alterations in the immune response to EBV (poor-quality immunity) that can favor viral reactivation, escalating the risk for developing EBV-associated B-cell lymphomas.